The importance of medicinal plants for the Algodoal fishing community - Roman, André Luís Cote; dos Santos, João Ubiratan Moreira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Over the past three decades the fishermen of the Salgado, region on the Pará coast, have experienced a process of cultural, social and economic change, although the use of plants for various purposes has persisted. The aims of this study were to identify the species of restinga which are most widely used for medicinal purposes by the residents of Algodoal, a fishing community located in the region in question, and to test ethnobotanical techiniques designed for this objective. During the study, 24 species with medicinal properties were identified, of which eight were outstanding in terms of cultural importance.
Keywords: Restinga; Amazônia; Fishing community; Medicinal plants; Ethnobotany